Covalent biofunctionalization of chitosan nanofibers with trypsin for high enzyme stability - Slováková, Marcela; Srbová, Jana; Křípalová, Zuzana; Žárská, Monika; Špačková, Martina; Stránská, Denisa; Bílková, Zuzana (Elsevier Science BV, 2016)
The electrospun chitosan nanofibers provide excellent material for immobilized proteolytic enzymes, and are biocompatible, nontoxic and hydrophilic matrices with large specific area. This paper deals with an application of electrospun chitosan nanofibers and optimizing conditions for their biofunctionalization by model proteolytic enzyme trypsin. Nanofibers fromchitosan were prepared using Nanospider™ technology and covalent immobilization of trypsin followed. Three immobilization techniques preserving biocompatibility and utilizing amine and/or hydroxyl groups of chitosan were optimized and compared to simple adsorption to achieve maximum proteolytic activity per cm2 of the functionalized chitosan nanofibers (Tryp-NF). Significant differences were observed. Trypsin immobilized by the carbodiimide one-step protocol demonstrated the highest activity of the three procedures, ranging from 132 to 210 IU/cm2 (i.e., 548–874 IU/mg of nanofibers), depending on the initial amount of trypsin used. Long-term storage stability together with high reusability of Tryp-NF confirmed advantages of the immobilized enzyme. Tryp-NF showed no cytotoxicity toward growth of HeLa cells. The in vivo tests for irritation and skin sensitization demonstrated no undesirable skin reactions.
Kovalentní biofunkcionalizace chitosanových nanovláken s trypsinem s vysokou enzymovou stabilitou
Keywords: trypsin; chitosan; electrospun nanofibers; reusability; biofunctionalization